O-024 Clinical outcome in stent versus balloon assisted unruptured aneurysm coiling in the ECOSA Multicenter Study. (16th November 2010) - Owais, M; Zaidat, O; Noquiera, R; Levy, E; Xavier, A; Linfante, I; Gupta, R; Edgle, R; Nguyen, T; Mueller-Kronast, N; Tong, F C; Hsu, D P; et al.
Abstract : Background and objective: Cerebral aneurysm with endovascular coil embolization is a well established treatment modality. Endovascular therapy can be complex with primary coiling versus stent or balloon assisted coil embolization. Limited data exist that compares the safety and clinical outcome of balloon versus stent assisted coiling of cerebral aneurysm. This is a substudy of the large Endovascular Coil Embolization of Small Unruptured Cerebral Aneurysm (ECOSA) study comparing stenting versus balloon assisted coiling in a large multicenter cohort. Method: Data from 11 US medical centers are collected on technical and procedural outcome of unruptured small cerebral aneurysm coiling (<7 mm) with the selection for comparison the subgroups of stenting and balloon assisted coiling. Data on clinical baseline variables and periprocedural outcome of thromboembolic event (TEE) and procedural rupture is collected and compared between the two groups in univariate and multivariate analysis Results: 351 patients were identified to have an adjunctive device use for coiling cerebral aneurysm. 247 underwent stent assisted coiling and 104 underwent balloon assisted coiling. Mean age of the stenting group was 55.6±11 versus 53.5±12.5 for the balloon group (p value 0.06). The majority were women with 75.7% in the stenting and 77.8% in the balloon group, and the majority were white (73.4%). Mean size of the aneurysm in the stenting group was 5 mm±1.2 mm versus 4.6 1.2 mm for the balloon (p=0.003). Overall events rate of all TEE and rupture complications were 4.2% for the stenting versus 1.6% for the balloon (p=0.02); there was a difference in the symptomatic complication of TEE or rupture. Conclusion: Contrary to the other literature, in our retrospective large case series comparing stent versus balloon assisted coiling, the event rate of TEE and rupture were significantly higher in the stent group. A larger prospective study is needed to confirm this result.